2021
DOI: 10.1371/journal.pone.0258882
|View full text |Cite
|
Sign up to set email alerts
|

Field testing two existing, standardized respiratory severity scores (LIBSS and ReSViNET) in infants presenting with acute respiratory illness to tertiary hospitals in Rwanda – a validation and inter-rater reliability study

Abstract: Introduction There is a substantial burden of respiratory disease in infants in the sub-Saharan Africa region. Many health care providers (HCPs) that initially receive infants with respiratory distress may not be adequately skilled to differentiate between mild, moderate and severe respiratory symptoms, which may contribute to poor management and outcome. Therefore, respiratory severity scores have the potential to contributing to address this gap. Objectives to field-test the use of two existing standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The original study that proposed the score retrospectively validated it in a small sample of 170 infants (<24 months) hospitalised in 3 centres in Spain with an acute respiratory infection; in this study they demonstrated that the score had good internal consistency, strong inter-rater reliability (between investigators and, between investigators and parents) and moderate construct validity [1]. Subsequently, a number of prospective external validation studies have been conducted showing similar results; studies assessing the validity of the clinician version of the ReSVinet score, that we are aware of, are summarised in Supplementary Table 1 [1,[5][6][7][8]. As such it currently appears to be one of the most promising and best validated severity scores for acute respiratory infections in infants.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…The original study that proposed the score retrospectively validated it in a small sample of 170 infants (<24 months) hospitalised in 3 centres in Spain with an acute respiratory infection; in this study they demonstrated that the score had good internal consistency, strong inter-rater reliability (between investigators and, between investigators and parents) and moderate construct validity [1]. Subsequently, a number of prospective external validation studies have been conducted showing similar results; studies assessing the validity of the clinician version of the ReSVinet score, that we are aware of, are summarised in Supplementary Table 1 [1,[5][6][7][8]. As such it currently appears to be one of the most promising and best validated severity scores for acute respiratory infections in infants.…”
Section: Introductionmentioning
confidence: 63%
“…For this study, we made use of three existing datasets. One recently published dataset was used to develop candidate simplified scores [11,12], and these scores were subsequently externally validated in three additional datasets, all of which have already been used to validate the original ReSVinet score and their findings published [5,13]. Further detail on each dataset can be found below; the inclusion and exclusion criteria of the datasets are listed in Supplementary Table 2.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] There are several validated scoring tools, though no tool has been universally recommended. [13][14][15] A large multicentre study found that protocols to limit HFNC decreased the odds of initiating HFNC and reduced the duration of HFNC and hospital LOS. 16 At our institution, HFNC is often initiated in the pediatric emergency department for patients with m/m disease, with significant variability among providers.…”
Section: Introductionmentioning
confidence: 99%